Microbiological Risks to Health Associated with the Release of Antibiotic-Resistant Bacteria and β-Lactam Antibiotics Through Hospital Wastewater - Andres E. Nolasco-Rojas; Eder Cruz-Del-Agua; Clemente Cruz-Cruz; Miguel Ángel Loyola-Cruz; Benjamín A. Ayil-Gutiérrez; María C. Tamayo-Ordóñez; Yahaira de J. Tamayo-Ordoñez; Araceli Rojas-Bernabé; Francisco A. Tamayo-Ordoñez; Emilio M. Durán-Manuel; Marianela Paredes-Mendoza; Laura M. Márquez-Valdelamar; et al. (Pathogens)
Hospital wastewater (HWW) is a major source of microbiological contamination, often released into the municipal sewage system without prior treatment. This HWW may contain pathogens with antimicrobial resistance, posing risks to public health. The aim of this work was to assess the risks associated with the seasonal release of ESKAPE bacteria resistant to β-lactam antibiotics and the release of carbapenems and cephalosporins through HWW of Hospital Juárez de México. The 12-month seasonal variation in β-lactam-resistant bacterial populations was assessed in the HWW of five discharge points. Resistant isolates were identified by mass spectrometry (MALDI-TOF) coupled with PCR assays to search for antimicrobial resistance genes, while β-lactamic antibiotics were detected using high-performance liquid chromatography (HPLC). Finally, a double-entry Vester matrix was constructed to classify the problems of HWW according to their degree of causality. Seasonal differences in bacterial loads were observed, with higher levels in warmer months. A wide variety of resistant pathogens were identified, including ESKAPE bacteria, as well as emerging bacteria carrying β-lactamase-encoding genes. The release of meropenem was detected most commonly, followed by cefepime and ceftazidime. The Vester matrix allowed the identification of critical clinical and environmental scenarios where two discharge points contribute significantly to the spread of microbiological contamination. This study highlights the importance of proper management of HWW and the need for stricter regulations to reduce the risks associated with the release of resistant pathogens with health impacts.